IS CONSERVATIVE TREATMENT OF HYPERTROPHIC CARDIOMYOPATHY AN ALTERNATIVE TO SURGICAL TREATMENT? - M. A. Gurevich (Российский кардиологический журнал)
Is conservative treatment of hypertrophic cardiomyopathy an alternative to surgical treatment?